Incorporation of crosslinked polydicyclopentadiene nanoparticles into epoxy thermosets via ring opening metathesis polymerization-induced self-assembly. (22nd August 2022) - Mei, Honggang; Hu, Jiawei; Gao, Yuan; Li, Lei; Zheng, Sixun
Abstract: In this contribution, we reported the generation of crosslinked polydicyclopentadiene nanoparticles in epoxy thermosets via polymerization-driven self-assembly approach. First, poly(ε-caprolactone)s (PCLs) with single cis -2-butene moieties in the main chains were synthesized, which were then employed as the macromolecular chain transfer agents (Macro-CTAs) for the ring-opening metathesis polymerization (ROMP) of dicyclopentadiene (DCPD). The ROMPs were carried out with the precursors of epoxy ( i.e., trimethylolpropane triglycidyl ether + 4, 4′-methylenebis(2-chloroaniline)) as the medium of dispersion. At a lower temperature ( e.g., 60 °C), the ROMPs were undergone completion and then the systems were heated to elevated temperature to start the curing reaction. It was found that the nanostructures were created in the cured thermosets, in which the crosslinked PDCPD nanoparticles were well dispersed in the thermosetting matrix. The crosslinked PDCPD nanoparticles displayed spherical, cylindrical and lamellar morphologies, influenced by the contents of modifier ( viz. DCPD + Macro-CTA) and the molecular weights of Macro-CTAs. Both dynamic light scattering and transmission electron microscopy showed that the generation of nanostructures followed a typical polymerization-induced self-assembly mechanism. Compared to plain epoxy, the nanostructured thermosets significantly displayed improved fracture toughness. The fracture toughness was readily modulated by controlling the contents of DCPD and the molecular weights of Macro-CTAs. Graphical abstract: Image 1 Highlights: ROMP-induced self-assembly was performed with epoxy precursors as dispersion medium. Crosslinked polydicyclopentadiene nanoparticles were generated in epoxy thermosets. The nanostructured epoxy thermosets displayed improved fracture toughness.